Access technique and its problems in parenteral nutrition – Guidelines on Parenteral Nutrition, Chapter 9 - Bischoff, S. C.; Braß, P.; Muehlebach, S.; Schregel, W.; Thul, P.; Pscheidl, E.; Working group for developing the guidelines for parenteral nutrition of The German Association for Nutritional Medicine; Volk, O.; Stanga, Z.; Jauch, K. W.; Hartl, W. (GMS German Medical Science, 2009)
Catheter type, access technique, and the catheter position should be selected considering to the anticipated duration of PN aiming at the lowest complication risks (infectious and non-infectious). Long-term (>7–10 days) parenteral nutrition (PN) requires central venous access whereas for PN <3 weeks percutaneously inserted catheters and for PN >3 weeks subcutaneous tunnelled catheters or port systems are appropriate. CVC (central venous catheter) should be flushed with isotonic NaCl solution before and after PN application and during CVC occlusions. Strict indications are required for central venous access placement and the catheter should be removed as soon as possible if not required any more. Blood samples should not to be taken from the CVC. If catheter infection is suspected, peripheral blood-culture samples and culture samples from each catheter lumen should be taken simultaneously. Removal of the CVC should be carried out immediately if there are pronounced signs of local infection at the insertion site and/or clinical suspicion of catheter-induced sepsis. In case PN is indicated for a short period (max. 7–10 days), a peripheral venous access can be used if no hyperosmolar solutions (>800 mosm/L) or solutions with a high titration acidity or alkalinity are used. A peripheral venous catheter (PVC) can remain in situ for as long as it is clinically required unless there are signs of inflammation at the insertion site.